Damage and restoration of historical urban walls: literature review and case of studies - Mauro Sassu; Aida Safabakhsh (Fracture and Structural Integrity)
Within this work, the causes of collapses and damages occurred in masonry artefacts have been evaluated to properly identify suitable monitoring and restoration methods. In this regard, a comprehensive literature review has been performed. Based on the results, moisture has been found to be a critical parameter, that affects the structural health of masonry artefacts. Various non-destructive methods were employed to measure moisture and monitor the materials involved, including Infrared Thermography, Electrical Resistivity Tomography, Ground Penetrating Radar, Laser Scanning and Digital Terrestrial Photogrammetry, Global Navigation Satellite Systems, Unilateral Nuclear Magnetic Resonance, Laser-Induced Fluorescence technique, Acoustic Imaging and Acoustic Tomography, Geographic Information System, on-site survey process and computer modeling of the structure with specific FEM software. Finally, the implementation of tie-beams, Fiber Reinforced Polymers layers, ventilation, draining systems, and high-quality materials are proposed as solutions for controlling the moisture effect and retrofitting.